Prospect of Redevelopment of the Showarighat Area of Dhaka Central Jail (Journal of Bangladesh Institute of Planners, 2017)
Dhaka Central Jail shifted to Keranigonj has enormous open land parcel, which is about 36.76 acres. It has been proposed to convert the old central jail place into public space. Such land use change will have an impact on the areas surrounding the central jail. A redevelopment plan is therefore required to control and guide this change in neighboring areas compatible with land use change of old central jail considering the aspirations of local residents. The purpose of this study is to ensure the participation of local people while preparing the redevelopment plan. In this regard, PRA tool is used while conducting the study. The study area is primarily a business hub with wholesale and retail activities and transport agencies. Small scale chemical industries are also visible in this area. Moreover, the area is bestowed with many inconveniences, like narrow road, traffic congestion, undesirable land use, water logging and lack of open spaces. In field survey, it is found that most local residents think that old central jail should be converted as a public space for recreational and community activities. Although different people have different views concerning the redevelopment, their opinions are accommodated in the proposals for redevelopment in this area.JBIP, Vol. 10, 2017 (Printed in December 2019), pp. 25-40